Kleine Bundesländer: Achillesferse des Föderalismus? - Andreas Müller; Holger Fricke; Norbert Berthold (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2006)
In this article we examine whether or not the small size (in terms of population) of some German Laender (states) is harmful. The economic theory of federalism forms the ground on which we present empirical evidence, focusing on our own results for the German Laender. We find evidence that political decisions on federal level instead of Laender level cause pref-erence costs, and so do decisions in big or merged Laender. On the other hand, economies of scale as an assumed advantage of big jurisdictions obviously do not influence the economic outcome very much. We do not find indications for strategic behaviour due to external effects either. Nonetheless, if external effects are regarded as a problem concerning "Stadtstaaten", they should rather be internalised by horizontal negotiations than by other instruments such as vertical payments or mergers between Laender. Hence, mergers of Laender do not seem to be a necessary precondition for decentralisation, which in turn is advisable as our results show.
Keywords: 330; Teilstaat; Finanzföderalismus; Deutschland